(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
To evaluate myocardial blood flow and identify regions of ischemia or infarction, Myocardial Perfusion Imaging (MPI) is a useful diagnostic technique. It relies on the identification of perfusion anomalies, which are related to underlying coronary artery disease and usually appear as regions of reduced blood flow. However, the appearance of paradoxical perfusion patterns in MPI raises doubt on the accepted interpretation of these imaging findings. Unexpected results in MPI are known as "paradoxical perfusion patterns," where regions of increased perfusion are found in places where decreased blood flow would be expected based on clinical presentation and conventional risk factors. Clinicians are faced with a diagnostic dilemma as a result of the unusual phenomena that have been documented in only a small number of cases. We are presenting two case reports that describe a paradoxical perfusion pattern seen during MPI. These cases raise questions about the traditional interpretation of MPI data and emphasize how crucial it is to take anatomical variations and collateral circulation into consideration when interpreting the results of perfusion imaging. Understanding the causes behind paradoxical patterns of perfusion is essential for proper diagnosis and appropriate therapeutic management, as it may affect treatment methods and prognosis. The reported cases conclude by emphasizing the need for careful interpretation of MPI findings to point out possible paradoxical perfusion patterns, which could be a symptom of particular anatomical differences. Keywords: Myocardial perfusion, paradoxical pattern, coronary artery disease, myocardial infarction, myocardial viability, stress tests. Bangladesh J. Nuclear Med. 27(1): 117-120, 2024